Model Komunikasi Pemasaran di Pemerintah: Promotion Mix Daerah Tujuan Wisata di Kabupaten Halmahera Barat - Lisda Ariani Simabur (Media Wisata, 2020)
Government Marketing Communication Model: Promotion Mix For Tourism Destinations In West Halmahera District. As One Of The Districts In North Maluku province, West Halmahera Regency has tourism potential, which is rich in beauty on land and at sea. Therefore, to introduce tourism potential to the community, a Marketing Communication Model in the Government is needed (Promotion Mix of Tourist Destination Areas in West Halmahera Regency). This study aimed to determine the integrated marketing communication strategy of the West Halmahera Regency Tourism Office in attracting tourists. This study uses a qualitative descriptive approach with analysis techniques through data collection, data reduction, data presentation, and the final step is concluding. The results found that the West Halmahera Regency Tourism Office's integrated marketing communication strategy uses four promotional mixes. Namely advertising (advertising), public relations (public relations), personal promotion (personal selling), direct marketing (direct marketing), and interactive marketing